A healthcare-associated outbreak of hepatitis C virus infections attributable to tampering injectable anaesthetic opioids, South Germany, 2017–2018 - Schmidt, Katarzyna; Böhm, Stefanie; Hesse, Raffaella; Bock, C.-Thomas; Haller, Sebastian; Katz, Katharina; Ross, Stefan; Timm, Jörg; Zimmermann, Ruth; Niendorf, Sandra (Frontiers in Public Health, 2025)
IntroductionIn October 2018, an outbreak of hepatitis C virus (HCV) in southern Germany was communicated to the Robert Koch Institute (RKI). Healthcare-associated transmission during invasive procedures involving a specific anaesthetist at a Bavarian hospital was suspected. The aim was to conduct a retrospective molecular outbreak investigation in order to elucidate the course of the outbreak.MethodsAn exposed patient was defined as a person who underwent a surgical procedure involving the anaesthetist in the Bavarian hospital from May 2016 to April 2018. A probable case was defined as an exposed patient with a positive HCV antibody test result and unknown HCV genotype. A confirmed case represented a probable case with hepatitis C genotype 3 (3a) infection. Descriptive epidemiological and phylogenetic analyses (using four HCV regions: Core, HVR1, NS5A and NS5B) were conducted.ResultsOf the 1,714 exposed patients, to whom HCV testing was recommended, 1,558 (90.9%) responded and were tested, 63 met the definition of a probable case, and 51 of those were confirmed cases. Sequencing data were available for 39 of the 51 confirmed cases. A sample from the anaesthetist was unavailable for further analysis. Phylogenetic analysis revealed close genetic relatedness of all 39 confirmed cases with identified HCV genotype 3a. Phylogenetic results indicated a common source of infection.DiscussionTo prevent healthcare-associated HCV transmission during anaesthetic procedures, protocols must document the amount of medication used and discarded. Regular staff testing and storing of clinical samples are also crucial for timely outbreak analysis and response.